PENERAPAN CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) PADA PELAJARAN MATEMATIKA DI TINGKAT PENDIDIKAN DASAR DI INDONESIA - Bebasari Amiroh; Daniel Ginting; Cindy Fortunasari (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2020)
This article aims to describe the fitness of Content and Language Integrated Learning (CLIL) in Mathematics subject for elementary education in Indonesia. The research was a qualitative study conducted through a case study. The case study was conducted in the context of elementary education. This research discovered that CLIL needed to be conducted in consideration of the urgency of teaching Mathematics in English, the appropriate method of teaching Mathematics in English, the appropriate duration of applying CLIL, and the impacts of CLIL on learners. Through the application of CLIL in teaching Mathematics in English, Indonesian students will be accustomed to the concept of understanding word problems in English, be accustomed to the application of higher order thinking in solving math problems, have higher interest in math and English, and have a stronger foundation for a more complex math learning at a higher level.